ANTEROLATERAL IMPINGEMENT OF THE ANKLE - ARTHROSCOPIC TREATMENT, CASE REPORT - Mladenović, Marko; Krstić, Andrija; Lalić, Ivica; Mladenovic, Desimir; Anđelković, Vladimir (Acta medicae Medianae, 2025)
In this paper, we present a patient who sustained an ankle injury without a fracture of the malleolus but with damage to the ligaments on the lateral side. The aim of this paper is to highlight the importance and role of the arthroscopic method in the treatment of ankle joint pathology.The patient was treated conservatively with a plaster cast and physical therapy. Six months after the injury, the patient continued to experience pain, limited dorsiflexion of the foot, and a reduced gait. An MRI of the ankle joint revealed an avulsion of the anterior talofibular ligament (ATFL) with a 6 x 4 mm bone fragment at its end, a capsule lesion, cartilage damage on the anterolateral side of the talus, and synovial hypertrophy of the ankle joint. The arthroscopic method was used to remove the hypertrophic synovium, free chondral bodies from the joint, scar tissue, and the bone fragment from the lateral sinus of the ankle. Consequently, the lateral recess of the ankle joint was decompressed and freed from all factors contributing to painful contact.The treatment outcome was excellent; pain disappeared, and complete foot function was restored.Ankle arthroscopy has advantages over the traditional surgical approach in the treatment of anterolateral ankle impingement following injury. It is a minimally invasive technique that preserves soft and bony tissues, allows for the removal of scar tissue and synovial and chondral lesions, and facilitates faster patient recovery.
Keywords: fibula apical avulsion, ankle arthroscopy, ankle impingement